Omics Multi-Layers Networks Provide Novel Mechanistic and Functional Insights Into Fat Storage and Lipid Metabolism in Poultry - Ghafouri, Farzad; Bahrami, Abolfazl; Sadeghi, Mostafa; Miraei-Ashtiani, Seyed Reza; Bakherad, Maryam; Barkema, Herman W.; Larose, Samantha (Frontiers in Genetics, 2021)
Fatty acid metabolism in poultry has a major impact on production and disease resistance traits. According to the high rate of interactions between lipid metabolism and its regulating properties, a holistic approach is necessary. To study omics multi-layers of adipose tissue and identification of genes and miRNAs involved in fat metabolism, storage and endocrine signaling pathways in two groups of broiler chickens with high and low abdominal fat, as well as high-throughput techniques were used. The Genegene-miRNA interacting bipartite and metabolic-signaling networks were reconstructed using their interactions. In the analysis of microarray and RNA-Seq data, 1835 genes were detected by comparing the identified genes with significant expression differences (p.adjust<0.01, fold change≥>2 and ≤<-2). Then, by comparing between different data sets, 34 genes and 19 miRNAs were detected as common and main nodes. The A literature mining approach was used and 7 genes were identified and added to the common gene set. Module finding revealed three important and functional modules which were involved in the PPAR signaling pathway, biosynthesis of unsaturated fatty acids, Alzheimer's disease metabolic pathway, adipocytokine, insulin, PI3K-Akt, mTOR and AMPK signaling pathway. This approach revealed a new insight to better understanding of the biological processes associated with adipose tissue.